The genetic architecture behind congenital heart disease: A review of genetic and epigenetic factors - Maaged A Akiel (Wolters Kluwer Medknow Publications, 2022)
Congenital heart disease (CHD) is the most frequently reported cause among miscarriages. Moreover, Infants born with CHD suffer from lifelong morbidity and have high risk of sudden infant death. The incidence of CHD is 8:1000, around 1% of live births worldwide. A wide range of environmental risk factors such as exposure to teratogens increase the risk for CHD through alterations in genetic and epigenetic networks governing heart development. Yet, a small subset of CHD is caused by inherited Mendelian mutations, copy number variations, or chromosomal abnormalities. Next generation sequencing technologies and chromosomal microarray analysis deciphered the genetic make-up of CHD. This review explains the genetic make-up of CHD and highlights key molecular genetics, cytogenetics, and epigenetics findings in syndromic and isolated CHD through analysis of inherited and sporadic genomic alterations.